(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Objective: A simple, precise, accurate, and rapid validated stability indicating high-performance thin-layer chromatography (HPTLC) method for estimation of Tenofovir Disproxil Fumerate was successfully developed. Materials and Methods: The method is based on HPTLC separation followed by densitometric measurements of their spots at 266 nm. This method is based on HPTLC separation followed by UV detection at 266 nm. The separation was carried out on merckTLC aluminum sheets precoated with silica gel 60F254 using a camag Linomat 5. Results and Discussion: The mobile consists of Butanol:Ethyl acetate: Acetic acid (4.5:0.5:0.3 v/v). Calibration curves were linear in the range of 300–1800 ng/band,respectively Tenofovir disoproxil fumarate gave sharp and well-defined peaks at Rf value are 0.51, respectively,stress degradation study shows that sample degraded with acid and base hydrolysis, under oxidation, thermal, and photolytic stress conditions. No chromatographic interferences from the tablet excipients were found. The method was validated in accordance with the requirements of International Conference on Harmonization guidelines Conclusion: Proposed method is precise, selective and accurate for the estimation of tenofovir disoproxil fumarate in the bulk and dosage form.